A molecular beacon real-time polymerase chain reaction assay for the identification of M. chitwoodi, M. fallax, and M. minor - Anderson, Scott D.; Gleason, Cynthia A. (Frontiers in Plant Science, 2023)
Root-knot nematodes (Meloidogyne spp.) are major pests of many important crops around the world. In the Northwestern region of the United States of America (USA), Meloidogyne chitwoodi causes economic losses in potatoes because the nematodes can infect the tubers, which leads to potato galling and reductions in marketable yield. Meloidogyne chitwoodi is a quarantine pathogen in certain potato export markets, and there is little industry tolerance for the presence of this nematode. Recently, two Meloidogyne species that are not known to be present in agricultural fields in the USA were detected on golf turfgrasses in California and Washington. These species, M. fallax and M. minor, are morphologically similar to M. chitwoodi and can infect potatoes and cause tuber damage. Their detection in the USA means that they could potentially infest potato fields and become a problem in potato production. Additionally, M. fallax is a regulated plant pest in the USA, which makes the correct identification of potato-infecting root-knot nematodes important. Previously, there was no single-tube assay that could determine whether M. chitwoodi, M. fallax, and/or M. minor were present in a sample. Thus, a molecular beacon real-time PCR assay which can reliably detect M. chitwoodi, M. fallax, or M. minor from crude nematode extracts was designed and characterized.